Antioxidant Activity of Combination Ethanol Extract of Turmeric Rhizome (Curcuma Domestica Val) and Ethanol Extract of Trengguli Bark (Cassia Fistula L) with DPPH Method - Triyono Triyono; Anis Yohana Chaerunisaa; Anas Subarnas (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Turmeric rhizome (Curcuma domestica Val) and Trengguli bark (Cassia fistula L) contain antioxidant compounds which can be determined by 1,1-Diphenyl-2- Pycrylhydrazyl (DPPH) free radical inhibition method. This research was conducted to determine DPPH free radical inhibition by ethanol extract of turmeric rhizome, the ethanol extract of trengguli bark, and a combination of turmeric rhizome extract - trengguli bark extract (1:1,5) with ascorbic acid as a comparison. Identification of secondary metabolite classes is performed by phytochemical screening. Antioxidant activity was performed by inhibition of free radical color of DPPH using UV-Vis spectrophotometry. The study showed IC50 value of ascorbic acid, as a comparasion, is 3,14 μg/mL. While ethanol extract of trengguli bark has the best antioxidant activity with IC50 value 10,98 μg/mL compare to combination ethanol extract of turmeric rhizome - trengguli bark (1 :1,5) and ethanol extract of turmeric rhizome with IC50 value is 13,70 μg/mL and 41,95 μg/mL, respectively.Keywords: Antioxidant, Curcuma domestica, Cassia fistula, DPPH Method